2019
DOI: 10.1016/j.psychres.2019.112486
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal subtypes, stress responsivity and impulsive aggression

Abstract: While prominent models of suicidal behavior emphasize the hypothalamic-pituitary-adrenal (HPA) axis dysregulation, studies examining its role have yielded contradictory results. One possible explanation is that suicide attempters are a heterogeneous group and HPA axis dysregulation plays a more important role only in a subset of suicidal individuals. HPA axis dysregulation also plays a role in impulsivity and aggression. We hypothesize subgroups of attempters, based on levels of impulsivity and aggression, wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 53 publications
0
18
0
4
Order By: Relevance
“…Their findings suggested that peer stress acts as a trigger for suicidal ideation among female youths, but only among those with blunted cortisol reactivity [ 41 ]. Recently, Stanley and colleagues [ 42 ] hypothesized that different subgroups of those who have attempted suicide may differ in HPA axis dysregulation. They explored baseline cortisol, total cortisol output, and cortisol reactivity in participants who had both a mood disorder and a suicide attempt history ( N = 35) and those with a suicide attempt history ( N = 37) during the TSST.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings suggested that peer stress acts as a trigger for suicidal ideation among female youths, but only among those with blunted cortisol reactivity [ 41 ]. Recently, Stanley and colleagues [ 42 ] hypothesized that different subgroups of those who have attempted suicide may differ in HPA axis dysregulation. They explored baseline cortisol, total cortisol output, and cortisol reactivity in participants who had both a mood disorder and a suicide attempt history ( N = 35) and those with a suicide attempt history ( N = 37) during the TSST.…”
Section: Resultsmentioning
confidence: 99%
“…They explored baseline cortisol, total cortisol output, and cortisol reactivity in participants who had both a mood disorder and a suicide attempt history ( N = 35) and those with a suicide attempt history ( N = 37) during the TSST. Specifically, those in the attempt group with higher impulsive aggression had a more pronounced cortisol response compared with other groups [ 42 ]. Additionally, Rizk and coworkers [ 43 ], in a sample of thirty-five individuals with major depressive disorder and 23 healthy controls, reported that individuals with brief, limited suicidal ideation (SI) are more stress-responsive (in the context of the TSST) than those with longer/continuous ideation.…”
Section: Resultsmentioning
confidence: 99%
“…Dysfunction of the biological stress response as suggested by hyperactive hypothalamic-pituitary-adrenal (HPA) axis responses has been evinced in both heavy alcohol users [ 88 90 ] and suicidal individuals [ 91 ] alike. Specifically, a subtype of suicide attempters high in trait impulsivity and aggression exhibited heightened cortisol responses to a lab-induced social stressor, compared to suicide attempters low on either aggression, impulsivity, or both [ 92 , 93 ]. Hyperactive cortisol responses have also been demonstrated in individuals with major depression [ 71 ], particularly in relation to symptoms of psychomotor agitation [ 94 ], and in individuals with highly variable patterns of suicidal ideation compared to those with stable suicidal thoughts [ 95 ].…”
Section: Alcoholmentioning
confidence: 99%
“…In the present study, we analysed three variables together with a correlation matrix and regression method, and all of the variables were included. In many previous studies, one of the variables was regarded as a group (36, [54][55][56][57]. A predictive model built to include impulsive personality, depressive symptoms and suicidal ideation shows that impulsive personality and depressive symptoms can explain the variance of suicidal ideation independently, but this model does not mention the correlation between impulsiveness and depressive symptoms (58).…”
Section: Discussionmentioning
confidence: 99%